2012
DOI: 10.1002/chem.201103332
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Assembly Directed by Metal–Aromatic Interactions: Control of the Aggregation and Photophysical Properties of Zn–Salen Complexes by Aromatic Mercuration

Abstract: There is widespread interest in non-covalent bonding and weak interactions, such as electrostatic interactions, hydrogen bonding, solvophobic/hydrophobic interactions, metal-metal interactions, and π-π stacking, to tune the molecular assembly of planar π-conjugated organic and inorganic molecules. Inspired by the roles of metal-aromatic interaction in biological systems, such as in ion channels and metalloproteins, herein, we report the first example of the use of Hg(2+) -aromatic interactions to selectively c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 75 publications
0
15
0
Order By: Relevance
“…ZnSalen has been employed for its high fluorescence with nonlinear optical properties, as well as its large two-photon absorption cross-section [232,233]. In 2012, Zhang's group demonstrated a two-photon activatable ZnSalen (Fig.…”
Section: Other Cell Organellesmentioning
confidence: 99%
“…ZnSalen has been employed for its high fluorescence with nonlinear optical properties, as well as its large two-photon absorption cross-section [232,233]. In 2012, Zhang's group demonstrated a two-photon activatable ZnSalen (Fig.…”
Section: Other Cell Organellesmentioning
confidence: 99%
“…16,17 We have recently reported that ZnSalens exhibit high fluorescence with nonlinear optical properties, which renders a platform for one-and two-photon fluorescent probes suitable for NIR excitation. [18][19][20] To increase the water-solubility of ZnSalen, we chose D-glucose as a neutral hydrophilic conjugate. In this work, ZnSalen conjugated with four glucose molecules, referred to as Zn-G 4 , was synthesized and well characterized by 1 H-NMR, IR, HR-MS and UV-vis spectrometries and spectroscopies (supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…In switching to a polar THF solution, the molecules of ZnL are under the influence of H-bonding with THF molecules. This would cause random aggregates of ZnL in THF, and hence the emission energy of ZnL is red shifted [16][17]. Instead, coordination to a Zn(II) center would enhance emission from the coordinating ligand.…”
Section: Luminescence Propertiesmentioning
confidence: 99%